Event-Triggered Output Feedback Control for a Class of Uncertain Nonlinear Systems - Xing, Lantao; Wen, Changyun; Liu, Zhitao; Su, Hongye; Cai, Jianping (IEEE transactions on automatic control, 2019)
In this paper, we investigate the problem of output feedback control for a class of uncertain nonlinear systems with event-triggered input. The considered system contains not only unknown system parameters, but also general nonlinear functions that are not required to be globally Lipschitz, in contrast to most of the existing results in the area. Besides providing two different event-triggered strategies without input-to-state stable assumption with respect to the measurement errors, we propose a new way to encode and decode the event-triggered control signals to further decrease the communication rate. With our newly proposed encoding-decoding mechanism, each time when the triggering event is violated, only 1-bit signal, either 1 or 0, is rendered to transmit through the communication channel between the controller and actuator. Clearly, this signal transmission mechanism is more effective and consumes less channel bandwidth. Through Lyapunov analyses, it is proved that the boundedness of all the signals is ensured and the output signal can be regulated to a compact set around zero, which is adjustable.